ESTIMATION RISK OF NAVIGATION - Кульбацкий, Андрей (SWorldJournal, 2020)
For research of use of special navigation aids (SNA) in the extreme situations connected to safety of navigation application of the mathematical modeling spent on the computer which allows to make quickly evident model is possible and to obtain the necess